2019
DOI: 10.1108/hff-11-2018-0714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the experimental and numerical analyses of silver nanofluid under influence of strong magnetic field

Abstract: Purpose Nanofluids’ properties made them interesting for various areas like engineering, medicine or cosmetology. Discussed here, research pertains to specific problem of heat transfer enhancement with application of the magnetic field. The main idea was to transfer high heat rates with utilization of nanofluids including metallic non-ferrous particles. The expectation was based on changed nanofluid properties. However, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…The use of nanofluids in natural and mixed convection has stimulated the interest of researchers (Bianco et al , 2019; Dutta et al , 2020; Fornalik-Wajs et al , 2020; Ghalambaz et al , 2019; Ait-Hssain et al , 2020; Doghmi et al , 2020; Goudarzi et al , 2020; Kadhim et al , 2020), because of its wide application both in nature and engineering technology. Most of the industrial processes are based on heat transfer, such as cooling electronic and mechanical components, heat transfer and flow in drying technologies, solar collectors and cooling of nuclear reactors, to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…The studies dedicated to the thermo-magnetic convection phenomena have expanded since then, combined with different branches of science, and reached new methodologies. The combination of active (magnetic field) and passive (addition of nanoparticles) heat transfer enhancement methods was reported in References [7,8]. The studies considering thermo-magnetic convection in rectangular cavities of various aspect ratios were presented in Reference [9].…”
Section: Introductionmentioning
confidence: 99%